2017
DOI: 10.1186/s12890-017-0443-1
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes is associated with an increased prevalence of respiratory symptoms as compared to the general population

Abstract: BackgroundTo estimate the prevalence of respiratory symptoms in individuals with type 2 diabetes, as compared to the general population.MethodsBetween 2007 and 2010 the screening questionnaire of GEIRD (Gene Environment Interactions in Respiratory Diseases) study was administered to two samples of Verona general population, aged respectively 45-64 years and 65-84 years, and to a convenience sample of individuals with type 2 diabetes, consequently recruited at the local Diabetes Centre. Ninety-four and 165 peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 39 publications
3
31
0
1
Order By: Relevance
“…Studies show that many people with type 2 diabetes also suffer from interstitial lung disease. The pro-inflammatory, proliferative, and oxidative properties of hyperglycemia have been shown to have an important role in affecting pulmonary vasculature, airways, and lung parenchyma [3][4][5]. But inflammatory lung diseases also can be a reason of glucose metabolism disorders.…”
Section: Resultsmentioning
confidence: 99%
“…Studies show that many people with type 2 diabetes also suffer from interstitial lung disease. The pro-inflammatory, proliferative, and oxidative properties of hyperglycemia have been shown to have an important role in affecting pulmonary vasculature, airways, and lung parenchyma [3][4][5]. But inflammatory lung diseases also can be a reason of glucose metabolism disorders.…”
Section: Resultsmentioning
confidence: 99%
“…An Australian prospective study which enrolled 1,108,982 individuals with diabetes indicated that standardized pneumonia mortality was 1.22-fold (95% confidence interval [CI], 1.17-1.27) higher in those with type 2 diabetes compared with general populations. 10 Moreover, Soubani et al 11 conducted a retrospective cohort study of ARDS patients, which showed that diabetes may not have effect on the mortality of ARDS patients. However, to our knowledge, little evidence was found about whether presence of diabetes was associated with higher mortality from respiratory diseases among Japanese populations.…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 8 Thus, the influence of diabetes on the disease-related outcomes still needs further study. Previous studies have demonstrated associations between diabetes and risk of mortality from respiratory diseases, such as chronic obstructive pulmonary disease (COPD), pneumonia, and acute respiratory distress syndrome (ARDS), 9 11 yet the results were inconclusive among different studies. Bragg et al 9 found that diabetes was significantly associated with increased mortality from chronic respiratory diseases, mainly COPD, through a nationwide prospective study of 512,869 adults in China (rate ratio 1.29; 95% CI, 1.10–1.51).…”
Section: Introductionmentioning
confidence: 99%
“…When the medical history data of the patients was analyzed with SPSS version 6.0, it showed no significant difference in both respiratory history and history of comorbidities was present between male and female (P > 0.05). People with type 2 diabetes more frequently reported grade 2 dyspnoea and chronic cough/phlegm than the general population of the same age, although presenting similar smoking habits 9 .…”
Section: Inclusive Criteriamentioning
confidence: 97%